Lake Chad Regional Economic Memorandum : Technical Paper 1. Socioeconomic Trends in the Lake Chad Region - Masaki, Takaaki; Rodríguez-Castelán, Carlos (World Bank, Washington, DC, 2021)
The Lake Chad region, which is an economically-and socially integrated area spanning across four countries of Chad, Cameroon, Niger, and Nigeria in north-west Africa, has been trapped in a vicious circle of suboptimal territorial development and fragility. This note shows that the Lake Chad region lags in multiple dimensions of development ranging from poverty, human capital, and access to services. A poverty rate in the Lake Chad region is found to be much higher than other parts of the countries surrounding the lake. The regional poverty rate in the Extreme North region of Cameroon (59 percent) is three times higher that of the rest of the country (19 percent). In Nigeria, the Lake Chad region203 has a poverty rate (72 percent) nearly twice as high as in the rest of the country (38 percent). Chad is the only exception, where the poverty rate in the country’s Lake Chad region (31 percent) is lower than the rest of the country (40 percent).204 This is explained by the fact that the Chad region around the lake lies near the capital of the country, with a consequently higher urbanization rate and a relatively high population density. The note is organized as follows. Section 2.2 provides key statistics on poverty, sector of work, and human capital indicators in the Lake Chad region vis-à-vis other parts of the country and examine how the Lake Chad lags behind in different dimensions. Section 2.3 provides a diagnostic of economic geography with a focus on three dimensions of density, distance and division. Section 2.4 identifies a set of structural factors, aggregate shocks and selected policies that might be associated with the dynamics of economic activity and social inclusion across the region.